Fogo Cruzado: olheiros do tráfico e campos de exceção - Zilda Manuela Onofri Patente (2021)
This master’s thesis aims to understand the camps of exception that raise around people on the streets and in harmful usage of drugs in Brazil. The ‘olheiros do tráfico’ are on the threshold between harmful usage and the association with illegal drug trade, thus they are the most exposed to prison, violence and extermination. Taking this into account, a biopolitical critique of the 'war on drugs' is proposed, analyzing the racist tactics which underlie the control of undesirable populations.